Nanofluid flow and heat transfer in corrugated backward-facing step channel using ethylene glycol as based fluid - Hilo, Al Behadili Ali Kareem (2020)
Experimental and numerical investigations are conducted to study the forced convection heat transfer and nanofluid flow through corrugated backward-facing step channels. Finite Volume Method (FVM) was used to solve the governing equation and the SIMPLE algorithm approach was applied. On 200 mm of the downstream wall, constant heat flux is applied, while the other walls are considered as isolated surfaces. Parameters such as corrugation shape (triangular, trapezoidal, and zigzag), amplitude height (1, 2, 3, 4, and 5 mm), pitch diameter (10, 20, 40, and 60 mm) and Reynolds number (Re) in the range of 5,000 to 20,000 were considered. The effect of CuO and MgO nanoparticles dispersed in pure ethylene glycol (EG) as a base fluid with diameters of 40 nm and volume concentrations of 0 to 5% on the fluid flow and heat transfer are investigated the length of the upstream wall of the channel was set to 200 mm and the length of the downstream wall was 300 mm. The height of the inlet and outlet were 10 mm and 20 ImTI, respectively. The expansion ratio is 2. The results reveal that combined a corrugated wall with a backward-facing step substantially improved the heat transfer, accompanied by a slight increment in the friction factor. The trapezoidal corrugated wall shows the highest enhancement in the heat transfer rate at 4 mm amplitude height and 20 mm pitch diameter. Combined the backward-facing step with corrugated wall enhanced the Nusselt number (Nu) up to 62% at Re = 5,000. The performance evaluation criteria increased as the amplitude height increases until it reached 4 mm and then decreased steeply. Moreover, the experimental results indicated that the heat transfer coefficient increases as the volume fraction of nanoparticles increased. The CuO-EG nanofluid enhances the Nusselt number up to II % compared to pure EG at a volume fraction of nanoparticles equal to 0.05. The friction factor of CuO nanofluid increases up to approximately 15% at volume fraction 0.01 and 0.03 and Reynolds number 5,000 and decreases as the Reynolds number increases. The maximum value of the performance evaluation criterion reached is 1.5 at a volume fraction of nanoparticles equal to 0.03 for the case of Cut) while it reaches 1.2 for the case ofMgO nanofluid.